MAKNA SIMBOLIK TRADISI UPAH- UPAH TONDI BATAK MANDAILING DI KOTA PEKANBARU - Nasution, Rofina Istiqamah; Salam, Noor Efni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
The tradition of wages is one of the cultural tondi contained in Mandailing Batak tribe. In tardisi tondi wages, there is a symbolic aspects that have a specific meaning that is represented by a tool or offerings and movements found in the tradition of wages Tondi. The purpose of this study was to determine the meaning of the symbolic situation, meaning the product of social interaction, and interpretation of the meaning of the tradition of wages tondi in Pekanbaru.This study uses a qualitative research approach symbolic interaction. The informants were 8 persons, namely 3 bamou (shamans), using techniques purpusive, and two members of the public who have tribes Pekanbaru city Batak Mandailing and three patients using the technique accidental. Data collected through observation, interview, and documentation.These results indicate that the meaning of the symbolic tradition of wage tondi situation in Pekanbaru city consists of physical objects and object physical sosial .Objek includes offerings or pangupah consisting of one chicken meaningful as expectations, the eggs meaningful wholeness, the tail head curry goat meaningful as a delicacy, liver meaningful as patience, vegetables and serves as the natural balance and the last sticky rice yellow bermakana as filfasat life, social objects include movement bamou in turnover tray itself him above the patient's head and serves as the life of absolute and mantras and chanting spoken by bamou on wages tradition -upah tondi who also have the specific meaning in every part like the implicit hope that people who are sick are given healing, social situations contained in wages tradition -upah tondi also have the special meaning that is meaningful togetherness.Prodak meaning of social interaction TradisiUpah- Wages tondi includes meanings of the bamou or traditional leaders where these traditions have the value of cultural, economic and spiritual while in terms of patients to make sense of this tradition have the value of culture, kepercayaa, spiritual and social values and of the general public have tribes tribes Batak Mandailing interpret this tradition has religious values, culture, and sosial.Makna interpretation TradisiUpah- tondi Wages include action open and closed action covered measures include internal and external motivations and feelings of patients and bamou. While open action includes facial expressions of bamou and patients.Keywords: Symbolic Meaning, Situation symbolic, Social Interpretation, Product social interaction, Wages Tondi